PROBLEMATIKA HUKUM YANG TIMBUL BERKAITAN DENGAN WEWENANG DISKRESI OLEH PENYIDIK UNTUK MEMILIH DAN MENENTUKAN “KETERANGAN AHLI” PORNOGRAFI - Ismu Gunadi (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
Authority of Diskresi by investigator in chosening and detemerning expert eyewitness or expert do not be supported clear legal fundament in practice the straightening of law role of investigator subyektif in environmental context [of] family embraced religion and also view having the character of person of especial factor; which is on its its have an effect on to justice decision which frequently exactly disagree with expectation justice of society that is light crime decision that is attempt crime.